2022
DOI: 10.1186/s12859-021-04550-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dynamic metabolomics data with multiway data analysis: a simulation study

Abstract: Background Analysis of dynamic metabolomics data holds the promise to improve our understanding of underlying mechanisms in metabolism. For example, it may detect changes in metabolism due to the onset of a disease. Dynamic or time-resolved metabolomics data can be arranged as a three-way array with entries organized according to a subjects mode, a metabolites mode and a time mode. While such time-evolving multiway data sets are increasingly collected, revealing the underlying mechanisms and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Extracted patterns are unique under mild conditions (25,37) and this facilitates interpretation. While CP-based tensor methods have been previously used in longitudinal data analysis, e.g., analysis of gut microbiome (38), urine metabolomics (39), and simulated dynamic metabolomics data (40), its application in postprandial metabolomics data analysis has been limited. We recently simulated postprandial metabolomics data using a human whole-body metabolic model (41), and demonstrated that analysis of the T0-corrected data (i.e., the postprandial data corrected by subtracting the fasting state data, similar to the method of analysis of changes ( 42)) using a CP model together with the analysis of the fasting state data provides a comprehensive picture of the underlying metabolic mechanisms.…”
Section: Significance Statementmentioning
confidence: 99%
“…Extracted patterns are unique under mild conditions (25,37) and this facilitates interpretation. While CP-based tensor methods have been previously used in longitudinal data analysis, e.g., analysis of gut microbiome (38), urine metabolomics (39), and simulated dynamic metabolomics data (40), its application in postprandial metabolomics data analysis has been limited. We recently simulated postprandial metabolomics data using a human whole-body metabolic model (41), and demonstrated that analysis of the T0-corrected data (i.e., the postprandial data corrected by subtracting the fasting state data, similar to the method of analysis of changes ( 42)) using a CP model together with the analysis of the fasting state data provides a comprehensive picture of the underlying metabolic mechanisms.…”
Section: Significance Statementmentioning
confidence: 99%
“…For instance, through the analysis of longitudinal metabolomics data as well as data from other sources, it may be possible to capture early signs of diseases (Price et al, 2017 ). Recently, tensor factorizations have been used to analyze dynamic metabolomics data (Li et al, 2022 ) but how to capture evolving patterns from such data is yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…The potential metabotype clusters identified using pDMDc were compared to clusters derived from the scores of the unconstrained CP ( 30 ), representing a state-of-the-art tensor decomposition method ( Equation 25 ).…”
Section: Methodsmentioning
confidence: 99%